주파수 변화 및 보조제 첨가에 따른 나프탈렌 및 페놀의 초음파 분해효율 비교 - 박종성(Jong Sung Park); 허남국(Nam Guk Her) (Daehan hwan'gyeong gonghag hoeji, 2010)
The research seeks to find the optimal conditions for sonodegradation of naphthalene and phenol as exemplary organic pollutants to be subjected to ultrasound in varying frequencies (28 kHz, 580 kHz, and 1,000 kHz) and in the presence of different kinds of additive (T$TiO_2$, $H_2O_2$, $FeSO_4$, Zeolite, and Cu). In cases of both naphthalene and phenol, 580 kHz of ultrasound has proven to be the most effective among others at sonodegradation. Based on the observation that OH radicals are also produced in maximum under exposure of 580 kHz of ultrasound, we concluded that this frequency of ultrasound creates hospitable condition for the combined process of degradation by pyrolysis and oxidization. $FeSO_4's$ degradation rate and k1 value have increased by approximately 1.8 times compared with the results of the solutions without any additives. This seems to be the result of ultrasound reaction which, accompanied by Fenton's reaction, increased the oxidative degradation and the production of OH radicals. However, application of ultrasound and Fenton's reaction is limited to the batch type conditions, as its use in continuous system can cause loss of iron or decay of the cistern, thereby creating additional pollutants. When the additive is replaced with $TiO_2$, on the contrary, the rate of sonodegradation has increased up to 20% compared to when there was no additive. We therefore conclude that $TiO_2$ could prove to be an effective additive for ultrasound degradation in continuous treatment system. 최근 초음파를 이용한 유기오염물질의 분해 연구가 진행 중이며, 보다 향상된 초음파 조건을 찾는 연구가 주목을 받고 있다. 본 연구에서는 초음파에 의한 분해 대상물질로 나프탈렌 및 페놀을 선정하여 다양한 주파수(28 kHz, 580 kHz, 1,000 kHz) 및 보조제($TiO_2$, $H_2O_2$, $FeSO_4$, Zeolite, Cu) 첨가 효과를 비교 분석하여 초음파 처리 시스템의 최적 분해효율 조건을 확인하였다. 주파수 변화에 따른 초음파 분해효율은 나프탈렌과 페놀 모두에서 580 kHz가 가장 우수한 효율을 보였으며, OH 라디칼 역시 동일 주파수에서 가장 많이 발생한 점을 미루어 볼 때, 580 kHz 근처의 초음파 영역에서 최적의 열분해 및 산화분해를 일으킬 수 있는 공동현상 조건이 형성된다는 것을 확인하였다. 100 mg/L의 다양한 보조제를 첨가하여 초음파 분해효율을 비교한 결과 $FeSO_4$의 분해효율 및 $k_1$값이 무첨가 초음파 반응에 비해 약 1.8배씩 우수하게 조사되었으며, 이것은 초음파와 펜톤 반응이 연계되어 OH 라디칼 생성을 촉진시켜 대상물질의 산화분해를 향상시킨 것으로 판단된다. 그러나 초음파와 펜톤 연계시스템은 배치식 조건에서만 제한적으로 적용 가능할 것이며, 연속식 초음파 시스템에서는 철의 손실, 반응조의 부식 및 새로운 오염물질을 발생시키는 문제를 야기할 수 있다. 이에 반해 $TiO_2$를 첨가한 초음파 분해속도가 무첨가 반응보다 약 20% 이상 향상된 점을 감안할 때, 초음파와 연계된 연속식 처리 공정에서는 $TiO_2$가 효과적인 보조제로 사용될 수 있을 것이다.